Acid Hydrolysis of Bis(2,2'; 6',2''–Terpyridyl) Iron(II) Complex in the Water Pools of CTAB/Hexane/Chloroform Reverse Micelles-A Kinetic Study in Confined Medium - K. V. Nagalakshmi; P. Shyamala (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
The kinetics of acid hydrolysis of bis(2,2';6',2''–terpyridyl) iron(II) complex has been studied in CTAB/Hexane/Chloroform reverse micelles. The reaction obeys first order kinetics with respect to each of the reactants at all values of W, {W= [H2O]/[CTAB]}. In the reverse micellar medium, the reaction is much slower compared to aqueous medium due to low micropolarity of the water pools which does not facilitate a reaction between reactants of same charge. The effect of variation of W {W=[H2O]/[CTAB]} at constant [CTAB] and variation of [CTAB] at fixed W has been studied. The second order rate constant (k2) of the reaction increases as the value of W increases up to W = 8.88 and remains constant thereafter and it is independent of concentration of [CTAB] at constant W. The variation of rate of reaction with W has been explained by considering variation of micropolarity and ionic strength of water pools of reverse micelles with W. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).